The utility of genotypic tropism testing in clinical practice. (July 2015) - Wyatt, H; Herman, OM; Macartney, M; Conibear, T; Garcia-Diaz, A; Booth, C; McCormick, A; Smith, C; Johnson, MA; Irish, D; Webster, DP
A review of a large number of HIV-1 tropism test requests ( n = 1148) performed at a London tertiary referral centre was carried out. The aim was to establish whether these were being performed in line with recommendations from published guidelines and whether this represented the most cost-effective use of these tests in informing prescribing decisions of the CCR5 antagonist drug, maraviroc. The cost of these assays within the UK was covered by commercial funding until April 2013 which has subsequently been withdrawn. Furthermore, all healthcare settings are under increasing cost constraints and hence establishing the real utility and appropriate use of these tests is of vital importance.